Perineal Wound Treatment with Wound Healing Process on Knowledge of Post Partum Mothers at the Bissappu Bantaeng Community Health Center - Qamarya, Nurul; Purbanova, Reni; Marwasariaty, Marwasariaty (International Journal of Health Sciences, 2024)
Maternal Mortality Rate is an important indicator in assessing health status. Maternal Mortality can be used in monitoring deaths related to pregnancy. This indicator is influenced by general health status, education and services during pregnancy and childbirth. The sensitivity of MMR to improvements in health services makes it an indicator of the success of health sector development. Cases of maternal death include deaths of pregnant women, giving birth and postpartum women. Perineal tears generally occur in the midline and can become extensive if the fetal head is born too early, the angle of the pubic arch is smaller than normal, the fetal head passes through the pelvic inlet with a size that is larger than the circumferential suboccipitobregmatica. A perineal wound is an injury to the urogenital diaphragm and leftator ani muscle, which occurs during normal delivery, or delivery with an instrument, and can occur without injury to the skin of the perineum or vagina, so it is not visible from the outside. The aim is to prove the relationship between post partum mothers' knowledge about perineal wound care and the wound healing process. This research method is an analytical survey with a cross sectional approach, the research population is all 32 post partum mothers at the Bissappu Community Health Center. The sampling technique in this research was carried out using a total population technique. The results of the study found that of the 32 respondents, the majority of respondents' knowledge about perineal wound care was sufficient, namely 15 people (46.9%) and the minority had good knowledge, namely 8 people (25%), normal wound healing, namely 12 people (37.5%) and the fast minority, namely 9 people (28.1%). Chi-Square test results (person Chi-Square) with a p value of 0.00 < α=0.05 where H0 is rejected and Ha is accepted. The conclusion is that there is a significant relationship between maternal knowledge about perineal wound care and the wound healing process.